Beliefs and outlook toward medications in Indian patients with very early rheumatoid arthritis: Cross sectional survey - Sakir Ahmed; Arup Mahapatra; Basanta Kumar Behera; Prasanta Padhan (Indian Journal of Rheumatology)
Introduction: Beliefs toward medicine influences drug compliance in rheumatoid arthritis (RA). Studies on attitudes toward medicine are available for established RA, where the disease itself could have altered the beliefs. Similar studies are not available for early RA. Thus, we surveyed patients with very early RA to determine their initial outlook toward medicines. Methods: Two hundred and fifty patients fulfilling the American College of Rheumatology/European League against Rheumatism 2010 criteria for RA, who had developed arthritis within the past 3 months were surveyed using the Beliefs about Medicines Questionnaire (BMQ). For the BMQ subsets (specific necessity, specific concern, general overuse, and general harm), more than scale midpoint is considered high. Depending on these scores, patients were classified as indifferent, accepting, sceptical, or ambivalent. Correlations of these scores with age, sex, time to presentation, education, occupation, and income were calculated. Results: Mean (±standard deviation) age of the cohort was 47.6 (±13.4) years with 88.4% (221) being females. Twelve (4.8%) had a high specific necessity, while 31 (12.4%) had a high specific concern score. General overuse and general harm scores were high in 248 (99.2%) and 246 (98.4%) patients, respectively. Thus, 242 (96.8%) patients were classified as indifferent, 4 (1.6%) accepting, 4 (1.6%) sceptical, and none as ambivalent. There was no statistically significant correlation between these scores and sex, age, educational status, occupation, or income. Multivariate analysis showed that persons with high specific concerns about medicines, educated to secondary level, being a student or having a desk job tended to present earlier. Conclusion: General harm and overuse scores were high, but patients had low scores on the scales specific for RA medication. Thus, most of them were classifiable as “indifferent” unlike as in previous studies on established RA.